JIWA ENTREPRENERSHIP TUMBUH DIKALANGAN SANTRI PONDOK PESANTREN BAKTI BAPAK EMAK JOMBANG MELALUI KEGIATAN SAMBUNG DINI BIBIT DURIAN LOKAL (BIDO) - Haryanti, Erna; Inti, Ristani Widya; Siswati, Endang; Anggraeni, Adelia Tri; Giawa, Trisman Jaya (Indonesian Collaboration Journal of Community Services (ICJCS), 2024)
The community service, which was carried out at the Bakti Bapak Emak Islamic Boarding School Jombang, completed the Indonesian World Records Museum (MURI) activity for the highest number of durian (bido) seeds early grafting. Also Encourages sense of entreprenership for students at the Bakti Bapak Emak Islamic Boarding School, Jombang.so that early grafting of durian seeds can be developed into a business that not only aims to preserve local durian germplasm, but also becomes a business venture that is competitive, profitable and sustainable. To foster entrepreneurial motivation for the community and students at the Bakti Bapak Emak Islamic boarding school, it is carried out through extention activities about the importance of entrepreneurship, entrepreneurship techniques, competitive strategies and modern marketing techniques with digital marketing. Assistance and direct demonstrations were also provided regarding Bido durian grafting techniques. The target of this activity is to increase the students' knowledge and skills in entrepreneurship and mastery of durian grafting techniques, as well as the adoption of sustainable cultivation practices. The implementation of this community service applies community participation methods, namely the Participatory Rapid Rural Appraissal (PRRA) and Rapid and Rural Appraissal (RRA) methods, which provide an opportunity for the implementing team to work together to plan, organize, implement and control the implementation of this community service activity. The output targets of this community service activity are: 1) Early grafting technology for durian seeds can be implemented 2) the growth of entrepreneurial spirit in students and the community.